Membangun Jiwa Kreatif dengan Ilmu Kewirausahaan Untuk Siswa-Siswi SMK Sawunggalih Kutoarjo - Retno Sundari; Sapta Aji Sri Margiutomo (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Creative and innovative abilities are the foundation of an entrepreneurial spirit to achieve success. An entrepreneurial spirit can encourage an independent, creative and innovative mentality, responsibility and not giving up easily in starting a business. Providing an understanding of how to start an entrepreneur so that you can create your own job opportunities, reduce the level of unemployment due to waiting for work or negative thought patterns in yourself towards the business world. From the results of our observations, we can see that the problems that exist at Sawunggalih Kutoarjo Vocational School, it has become a basic need for them to understand the concept of entrepreneurship from an early age and utilize computer information technology to support their entrepreneurial needs. To support these needs, students need knowledge related to entrepreneurship. The end of this training activity is by giving a quiz on the material. Community Service activities were carried out by Sawunggalih Aji Polytechnic lecturers with the title "Building a Creative Spirit with Entrepreneurial Knowledge of Sawunggalih Kutoarjo Vocational School Students" with Sawunggalih Vocational School activity partners. This activity ran smoothly and the success of this activity was seen from the many responses in the form of questions and success in understanding the science of entrepreneurship and entrepreneurship.